Covalent Organic Framework Electrocatalysts for Clean Energy Conversion - Lin, Chun‐Yu; Zhang, Detao; Zhao, Zhenghang; Xia, Zhenhai (Advanced materials (Weinheim), 2018)
Covalent organic frameworks (COFs) are promising for catalysis, sensing, gas storage, adsorption, optoelectricity, etc. owning to the unprecedented combination of large surface area, high crystallinity, tunable pore size, and unique molecular architecture. Although COFs are in their initial research stage, progress has been made in the design and synthesis of COF‐based electrocatalysis for the oxygen reduction reaction, oxygen evolution reaction, hydrogen evolution reaction, and CO2 reduction in energy conversion and fuel generation. Design principles are also established for some of the COF materials toward rational design and rapid screening of the best electrocatalysts for a specific application. Herein, the recent advances in the design and synthesis of COF‐based catalysts for clean energy conversion and storage are presented. Future research directions and perspectives are also being discussed for the development of efficient COF‐based electrocatalysts. Covalent organic frameworks (COFs) are promising for catalysis, sensing, gas storage, etc., owing to their large surface area, high crystallinity, tunable pore sizes, and unique molecular architecture. Recent advances in the design and synthesis of COF‐based catalysts for clean energy conversion and storage are presented. Design principles and future research directions for development of efficient COF‐based electrocatalysts are also discussed.